The Influence of Macroeconomic Variables on the Performance of Sharia-Registered Stock Mutual Funds - Isnaeni Rokhayati; Siti Muntahanah; Harsuti Harsuti; Enrico Aziezy; Agung Prasetyo Minggi (AIBPM Publisher, 2026)
Sharia stock mutual funds are increasingly important investment instruments, but their performance remains sensitive to macroeconomic conditions. This study aims to test and analyze how macroeconomic variables, namely the BI rate, inflation, and exchange rate, influence the performance of Sharia stock mutual funds registered with the Financial Services Authority from 2016 to 2023. The sampling technique used purposive sampling, with 13 mutual funds as research samples. This quantitative panel-data study applied panel data regression, and the Random Effect Model was selected as the best model. The results show that the BI rate has a negative and significant effect on net asset value (NAV) (b = -2.352; p = 0.0005), while inflation has a positive and significant effect on NAV (b = 1.147; p = 0.0054). Meanwhile, the exchange rate has no significant effect on NAV (b = 0.769; p = 0.8113). These findings suggest that investors should consider interest-rate and inflation movements when making investment decisions in Sharia stock mutual funds, while future research may include internal fund characteristics, broader economic indicators, and taxation variables.